Impact of Pulmonary Rehabilitation on Quality of Life in Chronic Obstructive Pulmonary Disease (COPD) Patients - Mohammed Abdullah Muarrij,; Metab Makhdoor Alsahfi,; Mohammed Aqeel Albaqawi,; Fatimah Foud Abualsaud,; Shaima Abkr Mesawa,; Muhannad Mohsen Alzahrani,; Abdulhadi Ali Alghamdi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Pulmonary rehabilitation has been the leading approach to treatment in COPD, but in this investigation, it has been significantly enriched in physical, psychological, and social aspects for the patients. The current paper detected the key place of physical training, education, psychological support, and socialization in an increase of the quality of life of COPD sufferers. Physical training increases cardiopulmonary and muscle endurance, decreases dyspnea, and thus promotes daily functioning. It provides the patient with an education on how to manage the disease themselves, how to avoid worsening of their condition; hence, controlling it. Psychological support appeases anxiety and depression, while social involvement restricts isolation and enables one to develop a sense of belonging to the community. Although accessibility, regarding both the location and cost, is a potential limitation to entry, virtual PR programs have emerged as yielding positive results; these provide comparable benefits with in-person rehabilitation. Thus, holistic treatment of COPD makes the position of pulmonary rehabilitation a must in the process of improving outcomes or ensuring quality of life.